The teachings of history of education (m-ped/02) for training of teachers. A comparative perspective - Pruneri, Fabio (Rivista di Storia dell’Educazione, 2019)
This article is based on data collected through mapping of teachings in the History of Education (M-Ped / 02) at Italian universities. Its research questions are twofold: to what extent do the teachings in this discipline respond to demands in terms of the preparation of Italian primary and secondary teachers? What is the condition of such History of Education-related teachings worldwide? The answer to these questions is gained from re-visiting national and international debates on the educational value of the history of education.